Facebook as Social Media Tools among Muslim Youths in Malaysia - Muhamad Zaki Mustafa; Zainol Abidin Ahmad; Zulkiple Abd Ghani; Abdul Rahim Zumrah; Roslizawati Mohd Ramly; Wan Mohd Fazrul Azdi Wan Razali (Center for Promoting Ideas, 2024)
Volume: 2 No: 8 (page: 173-177)